Aboriginal burning promotes fine-scale pyrodiversity and native predators in Australia's Western Desert. (March 2018) - Bliege Bird, Rebecca; Bird, Douglas W.; Fernandez, Luis E.; Taylor, Nyalanka; Taylor, Wakka; Nimmo, Dale
Abstract: Both invasive mesopredators and altered fire regimes impact populations of vulnerable native species. Understanding how these forces interact is critical for designing better conservation measures for endangered species. This study draws on Indigenous ecological knowledge and practice to explore heterogeneity in faunal responses to Indigenously managed landscapes in the Western Desert of Australia. Using track plot surveys and satellite image analysis of fire histories, we find evidence that pyrodiversity increases activity measures of dingoes and monitor lizards. Dingoes were more active in recently burnt patches, while foxes were more active in slightly older burnt patches. These results add to previous work showing significant effects of pyrodiversity on kangaroo populations in the region. Together, the findings suggest that Aboriginal burning not only creates diverse niches for native animals, it helps to facilitate the ecological role of species that are themselves functionally vital. This work adds to a growing body of research suggesting that the loss of Aboriginal burning can cascade through ecosystems by transforming and simplifying ecological networks, thus contributing to the decline and extinction of vulnerable species. Highlights: We assessed predator responses to fire diversity and fire history to test whether patch mosaic burning affects populations of some native species. We characterized fire diversity using ethnoecological categories defined by Aboriginal Australian traditional owners of the region. Pyrodiversity increased dingo and monitor lizard activity but had no effect on cats and foxes. Dingos preferred newly burnt patches while cats and foxes avoided them; monitor lizards preferred long unburnt patches. By favoring dingos, Aboriginal mosaic burning may be critical for the conservation of native species vulnerable to invasive mesopredators.